Authoring personal histories: Exploring the timeline as a framework for meaning making - Thiry, Elizabeth; Lindley, Siân; Banks, Richard; Regan, Tim (Proceedings of the 2013 SIGCHI conference on Human Factors in computing systems (CHI 2013), 2013)
It has been argued that technologies for ‘memory’ should be designed to support creativity and meaning building, rather than the passive capture of cues for remembering [25]. We report findings from a study inspired by this in-sight, in which older people made personal digital timelines using a new tool called Project Greenwich. We explore how the constraints of the timeline metaphor offer a framework for authoring, and examine how timelines can be used to underpin meaning building in relation to personal content. We highlight the importance of making, this being a vehicle for connecting with others in the present, and a potential means of emphasizing those elements of the past felt to be most salient when looking back.